Multimodality Imaging of a Giant Aortic Valve Papillary Fibroelastoma - Nowell M. Fine; David A. Foley; Jerome F. Breen; Joseph J. Maleszewski (Case Reports in Medicine)
Papillary fibroelastomas (PFEs) are benign cardiac tumors arising from endocardium. They are commonly found on valvular surfaces and average 1.0–1.5 cm in size. Though often asymptomatic, PFEs can lead to potentially severe complications, primarily due to their embolic potential. Surgical resection is recommended for all symptomatic or large PFEs. We report the case of a patient presenting with cardiovascular symptoms who was found to have a very large aortic valve PFE, as diagnosed by histopathologic examination following surgical resection. Multimodality cardiovascular imaging demonstrates the classic morphologic findings, including a pedunculated appearance and oscillating “frond-like” surface projections.